Economic Crisis and Informatisation Strategies of Enterprises : Results of a Survey with a Focus on SME Sector - Dyczkowski, Mirosław (Advanced Information Technologies for Management – AITM 2009, 2009)
The paper discusses results of a survey carried out in April-May 2009 which aimed it analysing how the recent economic crisis influenced informatisation strategies of enterprises. The initial part presents assumptions for the research project. It is followed by multidimensional statistical analysis of 139 collected sets of data. The results obtained support a working hypothesis that the economic crisis affected to smaller or greater extent short- and long-range informatisation strategies n the majority of companies or institutions. The visible signs of that situations include: decreasing budgets and employment in IT departments, limited spendings on IT investments, reduced scopes of ongoing projects, postponed or suspended IT investments, abandoned investment plans, or substantial cuts in seminars and trainings related to information technology.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 77-95